Health Equity in Lebanon : A Microeconomic Analysis - Salti, N. (2012)
Background: The health sector in Lebanon suffers from high levels of spending and is acknowledged to be a source of fiscal waste. Lebanon initiated a series of health sector reforms which aim at containing the fiscal waste caused by high and inefficient public health expenditures. Yet these reforms do not address the issues of health equity in use and coverage of healthcare services, which appear to be acute. This paper takes a closer look at the micro-level inequities in the use of healthcare, in access, in ability to pay, and in some health outcomes. Methods: We use data from the 2004/2005 Multi Purpose Survey of Households in Lebanon to conduct health equity analysis, including equity in need, access and outcomes. We briefly describe the data and explain some of its limitations. We examine, in turn, and using standardization techniques, the equity in health care utilization, the impact of catastrophic health payments on household wellbeing, the effect of health payment on household impoverishment, the equity implications of existing health financing methods, and health characteristics by geographical region. Results: We find that the incidence of disability decreases steadily across expenditure quintiles, whereas the incidence of chronic disease shows the opposite pattern, which may be an indication of better diagnostics for higher quintiles. The presence of any health-related expenditure is regressive while the magnitude of out-of-pocket expenditures on health is progressive. Spending on health is found to be "normal" and income-elastic. Catastrophic health payments are likelier among disadvantaged groups (in terms of income, geography and gender). However, the cash amounts of catastrophic payments are progressive. Poverty is associated with lower insurance coverage for both private and public insurance. While the insured seem to spend an average of almost LL93,000 ($62) on health a year in excess of the uninsured, they devote a smaller proportion of their expenditures to health. Conclusions: The lowest quintiles of expenditures per adult have less of an ability to pay out-of-pocket for healthcare, and yet incur healthcare expenditures more often than the wealthy. They have lower rates of insurance coverage, causing them to spend a larger proportion of their expenditures on health, and further confirming our results on the vulnerability of the bottom quintiles.